American National Election Study: 2016 Pilot Study ([Verlag nicht ermittelbar], 2016)
These data are being released as a preliminary version to facilitate early access to the study for research purposes. This collection has not been fully processed by ICPSR at this time, and data are released in the format provided by the principal investigators. As the study is processed and given enhanced features by ICPSR in the future, users will be able to download the updated versions of the study. Please report any data errors or problems to user support, and we will work with you to resolve any data-related issues. The American National Election Study (ANES): 2016 Pilot Study sought to test new instrumentation under consideration for potential inclusion in the ANES 2016 Time Series Study, as well as future ANES studies. Much of the content is based on proposals from the ANES user community submitted through the Online Commons page, found on the ANES home page. The survey included questions about preferences in the presidential primary, stereotyping, the economy, discrimination, race and racial consciousness, police use of force, and numerous policy issues, such as immigration law, health insurance, and federal spending. It was conducted on the Internet using the YouGov panel, an international market research firm that administers polls that collect information about politics, public affairs, products, brands, as well as other topics of general interest.